Pemanfaatan Media Sosial Sebagai Media Komunikasi Organisasi Ikatan Pelajar Muhammadiyah Leuwiliang Bogor - Mulkan Habibi; lutfi lutfi; R. Hiru Muhammad; Dissa Nur Adilla; Adetya Perdanaraya (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2023)
The use of social media for community organizations seems to be the most promising as an organizational communication facility because it can be a driving force to increase participation and democracy support. aims to produce IPM cadres who are ready to preach in the community. Communication messages on social media are on behalf of the organization, so the responsibility is not only on the individual but also on the organization, because in the organizational process usually the messages conveyed are organizational procedures. Therefore, social media must always prioritize the values ​​of integrity, professionalism, collegiality, politeness, and professional ethics. The success of every organization in achieving its goals is inseparable from the role of communication because through communication people in an organization will interact with each other, be it exchanging information giving opinions, instructions or motivating each other. The method used in this service activity is mentoring using social media wisely for da'wah activities. After holding this training, students are expected to know the ins and outs of how to use social media wisely and properly in using it, so as not to affect the wider community.